The role of methylprednisolone in severe COVID-19 patients: a meta-analysis - Xu, Wanru; Zeng, Yujun; Han, Hedong; Lv, Tangfeng; Lin, Dang (Frontiers in Medicine, 2024)
Background The purpose of this study is to assess the effectiveness of methylprednisolone in severe COVID-19. Methods PubMed, the Cochrane Library and Web of Science were searched for literatures comparing methylprednisolone and control treatment in severe COVID-19 patients. Statistical pooling was reported as risk ratio (RR) with corresponding 95% confidence interval (CI). The outcomes of interest in the literature survey were mortality and adverse events. Results A total of 13 studies were included, including 3,138 patients with severe COVID-19, of which 1,634 patients were treated with methylprednisolone and 1,504 patients were treated with control treatment. Five of the 13 studies reported severe adverse events. Our meta-analysis indicates that methylprednisolone treatment in COVID-19 patients is associated with a significant reduction in mortality (RR 0.62, 95% CI 0.46–0.85, p = 0.003) compared to control treatment, without an increased risk of adverse events (RR 1.20, 95% CI 0.92–1.56, p = 0.17). Moreover, high-dose methylprednisolone treatment (RR 0.57; 95% CI 0.40–0.82, p = 0.003) and short-course methylprednisolone treatment (RR 0.54; 95% CI 0.38–0.89, p = 0.01) found to significantly reduce mortality. Additionally, it was found that younger severe COVID-19 patients (RR 0.40; 95% CI 0.20–0.80, p = 0.01) had better outcomes to methylprednisolone than older patients. Conclusion Methylprednisolone was correlated with lower mortality compared with control treatment in severe COVID-19 patients without increasing serious adverse reactions. Furthermore, high-doses and short-term of methylprednisolone treatment were linked with better younger COVID-19 reported higher benefit from methylprednisolone than older COVID-19 patients.